THE INFLUENCE OF MACROECONOMICS AND ESG PERFORMANCE ON FINANCIAL DISTRESS IN COMPANIES LISTED IN THE SRI-KEHATI INDEX - Raihani Mufti Zamaya; Rindang Matoati; Farida Ratna Dewi; Eka Dasra Viana4; Budi Purwanto (STABILITY : Journal of Management and Business, 2026)
Global and national economic conditions constantly fluctuate due to government policies, natural conditions, politics, and market sentiment. Such economic downturns can affect corporate financial stability. Companies that fail to implement appropriate strategies during these conditions are vulnerable to financial distress. Implementing Environmental, Social, and Governance (ESG) aspects can serve as a mitigating factor against the risk of financial distress caused by macroeconomic shocks. This study aims to analyze the macroeconomic effects—proxied by inflation, exchange rates, and economic growth—and ESG performance on financial distress in companies listed on the SRI-KEHATI Index during the 2020–2024 period. The sampling method employed is purposive sampling. The data analysis method used is panel data regression processed using EViews 12. The results indicate that inflation has a significant positive effect on financial distress, and ESG performance has a significant negative effect on financial distress. Meanwhile, exchange rates and economic growth have no significant effect on financial distress.